1991
DOI: 10.1002/pen.760311704
|View full text |Cite
|
Sign up to set email alerts
|

Application of the microbond technique: Characterization of carbon fiber‐epoxy interfaces

Abstract: Microbonding has been applied to measure the interfacial shear strength, r , between single carbon fiber and microdroplets of epoxy resins. The effect of thermoset cure and resin modification on this initial parameter for composite performance have been studied. The interfacial shear strength for the host fiber/epoxy system (T-300/Epon 828) increased 3 fold from a B-stage to a fully cured material. The addition of a toughening agent called "Fortifier P" to the host resin system increased T by 40%. Residual the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The combination of adding a coupling agent and removing the epoxy sizing yielded the highest IFSS, where the effects of adding the coupling agent were more significant than removing the sizing agent. The addition of the coupling agent brought the IFSS values for the carbon fibre/polypropylene system in line with values reported in the literature for VCF epoxy [26,38,39]. The XPS analysis of the surface composition indicated an increase in nitrogen at the surface of the desized fibres.…”
Section: The Effect Of Coupling Agentsupporting
confidence: 85%
See 1 more Smart Citation
“…The combination of adding a coupling agent and removing the epoxy sizing yielded the highest IFSS, where the effects of adding the coupling agent were more significant than removing the sizing agent. The addition of the coupling agent brought the IFSS values for the carbon fibre/polypropylene system in line with values reported in the literature for VCF epoxy [26,38,39]. The XPS analysis of the surface composition indicated an increase in nitrogen at the surface of the desized fibres.…”
Section: The Effect Of Coupling Agentsupporting
confidence: 85%
“…Samples were produced using the virgin fibre (with epoxy sizing) only. It was found that the VCF.EP benchmark had an apparent IFSS of 45.8 ± 4.6 MPa, which is within the range of values reported in the literature for similar systems [26,38,39]. A summary of the recorded IFSS data is given in Table 2.…”
Section: Resultsmentioning
confidence: 48%
“…The reinforcements, matrices, the structure of the curing agents, curing mechanism, conditions and interfacial adhesion in the composites govern overall mechanical performance and durability of the materials. 23,24 G-EBCF-THPA possesses ß23% and ß 13% more tensile strength than those of G-EBCF-TCPA and G-EBCF-TBPA, respectively. G-EBCF-TBPA possesses ß23% and ß 21% more flexural strength than G-EBCF-THPA and G-EBCF-TCPA, respectively.…”
Section: Mechanical and Electrical Propertiesmentioning
confidence: 96%
“…The performance and durability of composites rely on strength and stiffness of the fibers, the strength and stability of matrix, and interfacial bond strength between fiber and matrix, fillers, compatibilizers and modifiers, fiber content, temperature, voids, dimensions, matrix material composition, fiber orientation, [36][37][38] etc. For engineering design, tensile properties are most widely used for quality characteristics.…”
Section: Mechanical Propertiesmentioning
confidence: 99%